Introduction to Traditional Houses Using Augmented Reality Based on Unity 3D on Android Platform - Rizky Bagas Prasetyo, Achmad; Dijaya, Rohman (Research Parks Publishers, 2025)
Indonesian culture is rich with traditional houses spread across the archip elago, serving not only as physical structures but also as symbols of history and cultural identity. Each traditional house has unique characteristics that reflect local wisdom and traditional life. However, modernization and urbanization threaten the continuity of many traditional houses, compounded by the lack of public appreciation for traditional cultural values. An innovative approach is needed to address these challenges, one of which is leveraging augmented reality (AR) technology. AR allows users to interact with virtual objects in the real world through electronic devices such as smartphones. AR technology, using Surface Tracking and visual inertial odometry (VIO), can be used to introduce and preserve traditional houses. This study, titled